Representasi Penggunaan Aplikasi Tiktok Terhadap Perilaku Belajar Peserta Didik - Dikna Sukriyati; Wawan (Prodi PAI IAILM Suryalaya, 2024)
Current technology affects all aspects of human life, especially a person's behavior. The purpose of this study was to determine the effect of using the religious Tiktok application on student learning behavior at SMA Serba Bakti Suryalaya Tasikmalaya. The research method used is a descriptive method with a quantitative approach. Sampling used a purposive sampling technique. Data collection techniques using observation, questionnaires and documentation. Based on the results of the study conducted, the influence of the use of the TikTok application on the learning behavior of SMA Serba Bakti Suryalaya students is 45.5%. And the remaining 54.5% is influenced by other variables outside this study, including internal factors such as physical condition, intelligence, talent and interests of students and external factors such as the student's environment. This study is also proven by testing the hypothesis with the t test, and produces a calculated t value of 4.832> t table 2.048 So it can be concluded that Ho is rejected and Ha is accepted which means